Pengaruh Kualitas Sumber Daya Insani Terhadap Etos Kerja Islam Karyawan Baitul Maal Hidayatullah Cabang Surabaya - Fauziyaturrahmah Fauziyaturrahmah; Qudsi Fauzi (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Basically the quality of human resources that owned by BMH employees branch of Surabaya is different. Islamic working environment would be a little more influence their motives in the work so that in the end the result is within their Islamic work ethic with Islamic values will be shown. This study aims to determine the effect of the quality of their human resources employees of Baitul Maal Hidayatullah branch of Surabayaagainst the Islamic work ethic.Is Islamic work ethic assessment results are influenced by the quality of human resources in the work.In carrying out this study the authors used a quantitative approach with a simple linear regression analysis model. The samples in this study were all employees of Baitul Maal Hidayatullah branch of Surabaya obtained saturation sampling method. Under this method obtained 42 employees. Data was collected by distributing questionnaires human resource quality and work ethic of Islam to employees. The results of this study indicate that the quality of human resources affect the work ethic of employees Baitul Maal Hidayatullah Islamic Branch of Surabaya.